(untitled) (Heritage, 2025)
Using the example of Kraljevo, we can see the intersection of global processes on a micro-social entity and explore how institutions at the local level acted in times of sudden crisis. By comparing and analyzing the activities of local governments in suppressing the smallpox epidemic in 1972 and the COVID-19 pandemic in 2020 and 2021, several significant differences and similarities can be noted. The difference in the types of tasks and methods of combating them arose from the nature of infectious diseases, the method and speed of transmission, the overall mortality they cause, and the territorial spread. One of the main differences in the methods of combating the epidemic and pandemic during the first months was the existence of vaccines. During the smallpox epidemic of 1972, in addition to rapid, comprehensive and effective immunization, an important task was the organization of quarantine for all those suspected of having been in contact with the infected. The Council for Public Health and Social Protection of the Municipal Assembly of Kraljevo, the Municipal Headquarters for Quarantine Diseases against Smallpox, as well as other local government bodies and competent institutions had tasks that arose from their competences, but the focus of the organization of the fight against smallpox was at higher, republican and federal levels. The smallpox epidemic was thus only a short-lived episode in the city’s history; fortunately, there were no casualties. Contrary to this, during the state of emergency caused by the COVID-19 pandemic, the local government had a wider range of operational tasks. The main role in organizing and coordinating the fight against COVID in Kraljevo was played by the City Emergency Headquarters. The results of its work in preventing the spread of the infection are also evident in the number of infected people in the period from March 15 to May 6, 2020. According to official reports, a total of 39 people infected with the COVID virus were registered in the aforementioned area, of which three people unfortunately died.